Carbon fiber-reinforced plastics based on epoxy resin toughened with core shell rubber impact modifiers - Park, Hyeongcheol; Jung, Hana; Yu, Jaesang; Park, Min; Kim, Seong Yun (WALTER DE GRUYTER GMBH, 2015)
The weak impact properties of carbon fiber-reinforced plastics (CFRPs) are due to their laminated structure, thus limiting the use of these materials in various automotive applications even though they provide weight savings as compared with metal materials. In this study, core shell rubbers (CSRs), which are known for their excellent dispersion characteristics, were selected as an impact modifier and CFRPs incorporated with CSRs were fabricated using the vacuum-assisted resin transfer molding process to enhance their impact properties. CFRPs with highly reinforced carbon fibers of 72-74 wt.% were prepared without voids as confirmed by morphological and thermogravimetric data. The impact strength of the CFRPs was improved by up to 87.5%, depending on the increase in CSR content, but their tensile properties were not reduced, indicating that these properties were predominantly determined by the continuous reinforcement of carbon fibers. Therefore, CSRs are an effective impact modifier for improving the impact properties of CFRPs. These findings will help in increasing the use of CFRPs as automotive structural materials.
Keywords: FRACTURE-BEHAVIOR; COMPOSITES; PARTICLES; MECHANISMS; POLYMERS; TOUGHNESS; BLENDS; DAMAGE